2018
DOI: 10.1002/jcph.1071
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Perspectives in Pharmacometric Models of Osteoporosis

Abstract: Osteoporosis is a disorder of the bones in which they are weakened to the extent that they become more prone to fracture. There are various forms of osteoporosis: some of them are induced by drugs, and others occur as a chronic progressive disorder as an individual gets older. As the median age of the population rises across the world, the chronic form of the bone disease is drawing attention as an important worldwide health issue. Developing new treatments for osteoporosis and comparing them with existing tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 99 publications
1
9
0
Order By: Relevance
“…It can also be seen that LSBMD (0.3 year) changes faster than THBMD (0.03 year). This is in line with the underlying bone physiology, where trabecular bone, which is more prevalent in the lumbar spine, is resorbed more rapidly than cortical bone, which is more prevalent in the hip 19,30 …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It can also be seen that LSBMD (0.3 year) changes faster than THBMD (0.03 year). This is in line with the underlying bone physiology, where trabecular bone, which is more prevalent in the lumbar spine, is resorbed more rapidly than cortical bone, which is more prevalent in the hip 19,30 …”
Section: Discussionsupporting
confidence: 76%
“…This is in line with the underlying bone physiology, where trabecular bone, which is more prevalent in the lumbar spine, is resorbed more rapidly than cortical bone, which is more prevalent in the hip. 19,30 Compared to the original bone cell interaction model by Lemaire et al, 16 which required >25 structural parameters to be identified and estimated, the mathematically reduced model required only 5 (z s , D A , k B , Plc max, and k Plc ), which made it applicable to clinical data. At the same time, the reduction in the degrees of freedom to be spent on the estimation of structural parameters allowed for the estimation of variance parameters as well as evaluation of covariate relationships.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by the FDA sought to justify the use of a modelling and simulation (M&S) approach in the development of drugs for osteoporosis . An important point of that review was the FDA's optimistic view on the use of an M&S approach to better appreciate the applicability of various surrogate markers to predict fracture risk.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of therapies is evident long after the initiation of treatment because improvements in bone strength require time. In contrast, changes in bone turnover markers (BTMs) are observed within a few weeks after the initiation of treatments, including bisphosphonate 3,4 …”
mentioning
confidence: 99%
“…In the osteoporosis field, several previous studies have shown the importance and use of modeling and simulation. For example, Madrasi et al 4 suggested that although both short‐term BTMs and long‐term BMD could predict fracture risk, BTMs may be more useful because they change faster than BMD. In addition, Bauer et al 5 and Vasikaran et al 6 reported that short‐term decreases in bone resorption markers could predict fracture risk.…”
mentioning
confidence: 99%